POTRET PENDIDIKAN KELUARGA DALAM AL-QUR’AN ( Telaah QS. AT-Tahrim Ayat 6 ) - Fakhrurrazi fakhrurrazi (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2018)
The Qur'an is one source of law and legal propositions. The Qur'an is a source of knowledge. Family coaching as the main pillar of Islamic education which is connected with Allah's command in the Qur'an, as in Q.S. At-Tahri>m [66]: 6, Allah commands those who believe to protect themselves and their families from the fire of hell, whose fuel consists of humans and stones, obediently and obediently carrying out the commands of Allah swt